Integrated school nutrition models: bridging school gardening, feeding and nutrition education - Hunter, Danny; Gonsalves, Julian; Anunciado, S.; Castro, R. (2024)
Presented at the Grassroots Partnerships for Pacific Solutions Conference in Nuku’alofa, Tonga, between 16-20 September 2024. This presentation focuses on the Integrated School Nutrition Model (ISNM) in the Philippines, which leverages crop museums as a key tool for educating children about food systems, nutrition, food safety and the environment; and can be used to supplement school meals.